THE UNPREPAREDNESS OF FARMERS IN FACING FLOOD DISASTER RISKS AS AN IMPACT OF CLIMATE CHANGE: A CASE STUDY IN BALONG, PONOROGO - Anggara, Yonatan Yolius; Sumunar, Dyah Respati Suryo; Khotimah, Nurul; Arif, Nursida (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2025)
Climate change-induced floods have significantly impacted agriculture in several villages of Balong Subdistrict, Ponorogo Regency. This study aims to (1) assess flood impacts on agricultural systems, (2) analyze farmers' unpreparedness for climate change, and (3) evaluate government policy responses in supporting flood resilience. Using a qualitative case study approach, data was collected through interviews with 13 farmers, 1 village head, 1 agricultural office staff, and 1 irrigation officer, supplemented by field observations and document analysis. Findings reveal 156 hectares of crops destroyed, with farmers maintaining traditional practices despite climate variability. Most farmers perceived floods as natural events rather than climate change consequences, while government responses emphasized reactive measures over long-term adaptation strategies. The study provides practical recommendations for integrated flood adaptation combining infrastructure improvement, farmer education, and policy reform. These findings offer valuable insights for enhancing climate resilience in flood-prone agricultural areas across Indonesia. Keywords: Climate Change Adaptation, Ponorogo, Flood Risk Disaster Management